RECUBRIMIENTOS DUROS EN MULTICAPAS DE Cr/CrN OBTENIDAS POR SPUTTERING CON MAGNETRÓN DESBALANCEADO (UBM) Y DIFERENTES GRADOS DE DESBALANCE - Piratoba, Ulises (MOMENTO, 2011)
Hard and tough coatings in the form of Cr/CrN bilayers were produced by reactive magnetron sputtering in Ar and Ar+N2 atmospheres respectively onto Si and Steel (H13) substrates. An unbalanced magnetron (GENCOA VT 100) and different Ar and N2 fluxes of 9 and 3 sccm respectively were used. The unbalanced geometric coefficient (KG) was varied between 1.37 and 0.87 by varying the magnetron position. Two series of coatings were produced. The first one of nine samples produced with three different bilayers periods and three different KG values and the second one with five samples produced with five different KG values. All coatings were characterized by x-ray diffraction (XRD), scanning electron microscopy (SEM) and atomic force microscopy (ATM). The coatings with thickness between 1.08 and 1.67 mm showed different surfaces with globular, ellipsoidal and piramidal formation. By increasing the unbalance increased the nano hardness, the growth rate and the particles size. However, the chemical composition and the diffraction planes did not show a definite tendency as a function of unbalance grade.